2012
DOI: 10.1002/rcm.6411
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation patterns of protonated amino acids formed by atmospheric pressure chemical ionization

Abstract: The relative abundances of the fragment ions increased with increase in the cone voltage. The experimental results were explained by the favorability of the intermediate structure and the stability of the fragment ion structure. The specific fragmentation patterns could be used for differentiating underivatized AAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 19 publications
2
22
0
1
Order By: Relevance
“…For comparison purpose, we have also recorded the CID spectra of [M + H] + ions of corresponding free amino acids (Table S3). The fragmentation pattern observed for [M + H] + ions of free amino acids was similar to those reported in the literature …”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…For comparison purpose, we have also recorded the CID spectra of [M + H] + ions of corresponding free amino acids (Table S3). The fragmentation pattern observed for [M + H] + ions of free amino acids was similar to those reported in the literature …”
Section: Resultssupporting
confidence: 79%
“…The fragmentation pattern observed for [M + H] + ions of free amino acids was similar to those reported in the literature. [17][18][19][20][21][22] We observed that the [M + H] + ions of all the dimethyl amino acids were fragmented at higher collision energies than those of corresponding free amino acids. The dimethyl amino acids showed primarily the elimination of (H 2 O + CO) in addition to other specific product ions due to methyl groups on nitrogen as well as the substituent (-R) on the α-carbon of the amino acids.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To target analytes containing a nonpolar hydrocarbon side chain, the main product observed is related a neutral loss of a formic acid [M + H – 46] + . On the other hand, quantifier ions of compounds such as GABA and tryptophan undergo a neutral loss of [M + H –17] + (NH 3 ).…”
Section: Resultsmentioning
confidence: 99%